Attitude tracking control for quadrotor UAVs based on extremum seeking - GUO Dali; ZHAO Zhongyuan; LUO Zijuan (智能科学与技术学报)
A robust control method based on extremum seeking is proposed for the attitude tracking problem of quadrotor UAV with uncertainty. Firstly, a nonlinear attitude model of a four rotor UAV was established, and considering the uncertainty of model parameters, a robust controller was designed to ensure the dynamic boundedness of tracking errors. Secondly, a learning-based controller was designed by combining a robust controller with a model-free learning algorithm, which automatically and iteratively adjusted the feedback gain of the robust controller and optimized the expected performance cost function online. Finally, numerical simulations were performed using MATLAB, which demonstrated a reduction of 0.246 in the steady-state tracking error of the proposed control method compared to the classical robust control method. This result confirms the robustness and superiority of the proposed method.